Hemicrania Continua - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1994)
Ten new patients and 24 previous reports of hemicrania continua are reviewed from the Albert Einstein College of Medicine, and the Montefiore Medical Center, Bronx, NY.